Contemporary perspectives on language and cultural diversity in early childhood education - Saracho, Olivia N.; Spodek, Bernard (Contemporary perspectives in early childhood education., 2010)
The purpose of the book series is to present reviews of current research in specific areas of early childhood education. Each volume is devoted to a particular area of the field. Within each volume scholars present reviews of research on particular aspects of the field of early childhood education. Each chapter summarizes the current research and provides an extended set of references which will facilitate readers in furthering their inquiries into research in that area. All contributions to each volume are juried, with an Editorial Board and additional scholars reviewing the draft chapters, suggesting ways that the chapters could be improved , and finally recommending them for publication. This process insures the quality of the contributions to the chapter and avoids the possibility of bias in the work.Recent findings suggest that young children's learning experiences are critical to their learning development, which has attracted the attention of researchers, scholars, and policy makers. Interest has focused on the early childhood policy and practice that can help improve the academic paths of children in poverty. Many of these children are from linguistically and culturally diverse families. The purpose of this volume is to review and summarize the current state of knowledge related to linguistically and culturally diverse children. It expanded cultural diversity to include social justice which can contribute knowledge in providing effective teacher preparation programs and high quality programs for linguistically and culturally diverse children.